Who is My Neighbour: Interfaith Dialogue and Theological Formation (Keynote Address) - Levine, Amy-Jill (Journal of the Council for Research on Religion, 2023)
“Who is my neighbour?” is a good question for both the Bible and today, but it is a complicated one. In this paper, I will focus on unpacking the idea of “love of neighbour,” first in its Levitical context, then in certain New Testament passages, and finally in contrast to its relationship with the concept of “stranger.” The term “neighbour” (רֵעַ) has multiple meanings in a Hebrew Bible context, and similarly, there are distinct meanings of “neighbour” within the New Testament – specifically between the gospels and the Pauline letters. I argue that the common understanding of the “Good Samaritan” passage, that Jesus promotes accepting everyone as neighbour, is incorrect; instead, I suggest that the literature demonstrates how a non-neighbour reveals how real neighbours should behave. The scope of the article is to demonstrate how discussions about “neighbour” and “stranger” can be used to segue into questions to dialogue between Christians and Jews.